2009
DOI: 10.3109/00016480903382808
|View full text |Cite
|
Sign up to set email alerts
|

Long-term course of Menière's disease revisited

Abstract: The frequency of vertigo attacks diminishes within 5-10 years. Hearing loss (of about 50-60 dB) and vestibular function decrement (of about 35-50%) take place mainly in the first 5-10 years of disease. Drop attacks may occur early or late in the course of the disease, and remission is spontaneous in cmost cases. Bilaterality of the condition increases with increasing duration of the disease (up to 35% within 10 years, up to 47% within 20 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(158 citation statements)
references
References 48 publications
5
141
2
10
Order By: Relevance
“…This shared aetiology between Meniere's disease and motion sickness may thus exaggerate sensory conflict during provocative motion stimuli. Bilateral Meniere's disease participants had higher levels of disease activity than unilateral, as indicated by increased numbers of vertigo attacks (Table 3), although others have found no difference [19,20]. We found that bilateral sufferers had higher motion sickness susceptibility than unilateral sufferers (MSC scores).…”
Section: Discussionsupporting
confidence: 52%
“…This shared aetiology between Meniere's disease and motion sickness may thus exaggerate sensory conflict during provocative motion stimuli. Bilateral Meniere's disease participants had higher levels of disease activity than unilateral, as indicated by increased numbers of vertigo attacks (Table 3), although others have found no difference [19,20]. We found that bilateral sufferers had higher motion sickness susceptibility than unilateral sufferers (MSC scores).…”
Section: Discussionsupporting
confidence: 52%
“…While the age of our patients were similar to elsewhere, we observed a male preponderance which is different from the equal male:female ratio [4] shown in the world literature. However a few reports have also shown a [6,3,7], female preponderance. Our findings could be because the male/female attendance in our audio vestibular clinic also has a male preponderance (2:1) and more men in India seek medical attention than women.…”
Section: Discussionmentioning
confidence: 98%
“…In world literature, the frequency of MD varies widely, with incidence ranging from 10 to 157 [2,3] per 100,000 in developed countries. The present study found that the frequency of MD in a tertiary level hospital is about 15.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Among his many research accomplishments was the development of tests to detect vestibular dysfunction, which currently affects tens of millions of people in the USA alone (Neuhauser and Lempert, 2009). Vestibular disorders range from bouts of vertigo that may last for minutes, to the chronic and debilitating effects of Ménière's disease, which in extreme cases results in balance and hearing impairment for life (Marom et al, 2009;Huppert et al, 2010). Most vestibular disorders are idiopathic in origin; however, in a subset of cases there is a clear developmental basis to the defect.…”
Section: Introductionmentioning
confidence: 99%